Legal Frameworks for Setting Aside Arbitral Awards in Taiwan and Indonesia: A Cross-Country Analysis - Umar, Wahyudi; Rasmuddin, Rasmuddin; Hamzah, Ismi Fadjriah; Wetzel, Matthias (Batulis Civil Law Review, 2025)
Introduction: Arbitration awards are one of the effective ways to resolve international business disputes. However, as in other countries, in Taiwan and Indonesia, arbitral awards may be annulled under certain conditions.Purposes of the Research: This study aims to conduct a cross-country analysis of the legal framework used to annul arbitral awards in Taiwan and Indonesia and evaluate the differences and similarities between the two countries.Methods of the Research: The research method used is normative legal research with a statutory approach.Results Main Findings of the Research: The results showed significant differences in the legal framework used to annul arbitral awards in Taiwan and Indonesia. In Taiwan, courts have broad authority to annul arbitral awards, whereas in Indonesia, courts can only annul arbitral awards under certain conditions. However, the two countries have similarities in the mechanism for the annulment of arbitral awards, such as the submission of annulment requests to the courts and the requirements and time limits that must be met to apply for an annulment.